Analysis of Factors that Explain Customer Satisfaction and Its Relationship with Repurchase Intention at Fresh Food E-Commerce in Jabodetabek Post Pandemic - Natania Agustin; Yekti Widyaningsih; Rianti Setiadi (Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Islam Bandung, 2025)
Abstract. Consumers now have the flexibility to purchase fresh food both online and offline in the post-pandemic era. In this competitive landscape, only companies that can retain their customers are likely to survive. This study investigates the factors influencing customer satisfaction and its impact on repurchase intention in the context of fresh food e-commerce. Specifically, it examines the effects of product quality, fair price, perceived ease of use, service response speed, and service convenience on customer satisfaction, and further explores the moderating role of customer experience in the relationship between satisfaction and repurchase intention. Primary data were collected using a purposive sampling technique from 160 respondents who had purchased fresh food from Sayurbox, Segari, Allofresh, or Astro within the last six months. Data was analyzed using Partial Least Square, a non-parametric statistical technique suitable for modeling latent variable relationships without distributional assumptions. The results show that product quality, fair price, service response speed, and service convenience significantly and positively influence customer satisfaction. In contrast, perceived ease of use does not have a significant effect. Customer satisfaction has a strong positive influence on repurchase intention. However, customer experience does not significantly moderate the relationship between customer satisfaction and repurchase intention. These findings highlight the importance of maintaining product and service quality to enhance customer satisfaction and encourage repeat purchases in the fresh food e-commerce sector.